2016
DOI: 10.1002/jso.24276
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of observed to predicted outcomes using the ACS NSQIP risk calculator in patients undergoing pancreaticoduodenectomy

Abstract: Background Postoperative outcomes predicted by the ACS NSQIP universal risk calculator have not been validated for specific procedures like pancreaticoduodenectomy (PD). Methods A random sample of 400 PD patients from the NSQIP database was analyzed. Patients were categorized into four groups of 100 each based on ICD-9 diagnosis (211.6, 157.0, 156.2, and 577.1). Estimated risks of postoperative outcomes recorded by the calculator were compared to observed outcomes using the Brier Score (BS). The calculated B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 24 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…Dahlke et al [ 9 ] reported good predictive accuracy of the ACS-NSQIP calculator in patients undergoing general and colon surgery. Similarly, Mogal et al [ 10 ] showed that the ACS-NSQIP calculator had good accuracy in predicting outcomes after pancreaticoduodenectomy, in spite of a slight variation between diagnostic groups. However, more recent studies have found limited predictive value of the ASC-NSQIP in patients undergoing other types of surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Dahlke et al [ 9 ] reported good predictive accuracy of the ACS-NSQIP calculator in patients undergoing general and colon surgery. Similarly, Mogal et al [ 10 ] showed that the ACS-NSQIP calculator had good accuracy in predicting outcomes after pancreaticoduodenectomy, in spite of a slight variation between diagnostic groups. However, more recent studies have found limited predictive value of the ASC-NSQIP in patients undergoing other types of surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…1 Significant improvements in diagnostic modalities, standardization in surgical techniques, and advancement in neoadjuvant and adjuvant therapies have led to a perioperative mortality rate of 2% and increased 5-y survival rates up to 27%. [2][3][4] Recent guidelines have recognized neoadjuvant chemoradiotherapy for localized pancreatic adenocarcinoma as the preferred treatment strategy with borderline resectable cancer and an acceptable treatment option for patients with potentially resectable cancer. [5][6][7][8][9] Proposed benefits of this approach include the selection of patients with favorable tumor biology, early treatment of micrometastatic disease, facilitation of a margin-negative resection, and maximal delivery of all components of multimodality therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A standardized, quantifiable measurement of frailty may inform clinicians of the patient's ability to tolerate surgical resection, and thus may improve patient outcomes. With the aim of identifying high‐risk surgical candidates, several preoperative risk prediction models have been proposed, such as the Physiological and Operative Scoring System for enumeration of Morbidity and mortality (POSSUM), Estimation of Physiologic Ability, and Surgical Stress Score (E‐PASS), NSQIP risk calculator, and comprehensive geriatric assessment (CGA) . However, these models have several disadvantages, as they are complex, time‐consuming, or inconsistent …”
Section: Introductionmentioning
confidence: 99%